2016
DOI: 10.21873/cgp.20011
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type-specific HPV Infections and hTERT DNA Methylation in Patients with Invasive Cervical Cancer

Abstract: Cervical cancer remains one of the most common cancers in women worldwide. According to GLOBOCAN statistics on cervical cancer (1), there were approximately 528,000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Epigenetic regulation of the hTERT gene could also be important to evaluate, as some researchers have shown that methylation play a key role in the regulation of hTERT, although contradictory results have been reported ( 40 43 ). Recently we have published an association between type specific HPV infections and hTERT methylation in patients with cervical cancer but additional studies in patients with HGSIL have to be done ( 44 ). In addition, lifestyle aspects including diet, exposure to stress, and level of physical activity can also produce changes in TA ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic regulation of the hTERT gene could also be important to evaluate, as some researchers have shown that methylation play a key role in the regulation of hTERT, although contradictory results have been reported ( 40 43 ). Recently we have published an association between type specific HPV infections and hTERT methylation in patients with cervical cancer but additional studies in patients with HGSIL have to be done ( 44 ). In addition, lifestyle aspects including diet, exposure to stress, and level of physical activity can also produce changes in TA ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, we speculated that the interaction of rs807181 and 807183 affected the ATG4A gene and down-regulated or inhibited its role in autophagy, which led to an increased susceptibility and ability of HPV to bind to the host. Some studies have shown that SNP-SNP interactions were notably associated with BMI ( 30 , 31 ), as well as colon cancer. The association between ATG4A genetic variations and HPV infection is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our studies showed that response to treatment, gene expression, and protein expression in the presence of high-risk HPV and variants of HPV-16 were linked. Through these studies, we contributed to the identification of predictive and prognostic biomarkers [ 10 15 ]. Recent analyses have aimed at improving the assessment of patients' individual risks [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%